Regioselective Synthesis of Isonitrile-Containing Densely Functionalized Alkenes from Propynenitriles - Jyoti, Jyoti; Jamra, Rahul; Deepika, Deepika; Sharma, Shreya; Malakar, Chandi C.; Singh, Virender (Synlett, 2025)
A transition-metal-free base-mediated approach has been devised for the synthesis of novel densely functionalized alkenes containing isocyanide, nitrile, and ester functionalities. The strategy was found to be applicable to gram-scale synthesis, and a library of functionalized alkenes with significant diversity was developed. The strategy could also be used for the synthesis of trisubstituted pyrrole derivatives by modifying the reaction conditions. The advantages of this approach are its operationally simple procedure, short reaction time (10–30 min), broad substrate scope, high atom economy, metal-free conditions, and high regioselectivity with good to excellent product yields.
Keywords: chlorovinyl aldehydes; propynenitriles; isocyanocyanoalkenoates; Michael addition; pyrroles; silver catalysis